On the high creep strength of the W containing IRIS-TiAl alloy at 850 °C. (December 2019) - Couret, Alain; Monchoux, Jean-Philippe; Caillard, Daniel
Abstract: This paper presents a study of the creep at 850 °C under 150 MPa of the IRIS alloy (Ti–Al48–W2–B0.1) densified by spark plasma sintering. The dislocation microstructure in a sample strained up to 1.5% was studied by post-mortem transmission electron microscopy. The deformation is mainly due to ordinary dislocations. Several populations of dislocations are evidenced. Their Burgers vectors, the plane in which they are moving and the corresponding deformation mechanisms are determined. In the discussion section, the deformation mechanisms, the factors controlling their activation and the role of tungsten as hardening element are examined. Graphical abstract: Image, graphical abstract